Heat transfer from a constant heat source to the plate surface: An analytical solution - Kucheva N.A. (E3S Web of Conferences, 2023)
This paper proposes an analytical solution to the thermoelasticity problem for a plate heated by a source with a constant heat input on one surface. Numerous comparisons were made between the results obtained on the basis of the analytical solution and the numerical one. When comparing the analytical and numerical solutions, it was shown that the advantage of the analytical solution is that it makes it possible to determine the greatest stress values over the entire heating time range, while using the numerical method it is necessary to perform a large number of calculations at fixed time values. However, the finite-element method allows for determining stresses in areas of the plate that are far from its centre, where the analytical solution proves to be unfair. Key words: , , , .